The Psychological Construct of Islamic Moderation Based on Tafsir Ulul Albab : A Comparative Study of Indonesia and Syria in Responding to Social Polarization - Nurzahara Sihombing; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Romaito Nasution; Milna Sari (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study aims to affirm the construct validity of Islamic moderation based on the tafsir of Ulul Albab through an empirical comparison between Indonesia and Syria in responding to the social polarization that divides contemporary societies. Through a comprehensive meta-analysis of 847 journal articles indexed in Scopus, Web of Science, and PsycINFO published between 2015 and 2024, the researchers examined data from 15,428 Indonesian respondents and 12,736 Syrian respondents, integrating cross-cultural quantitative findings within a rigorous statistical framework. The results of the confirmatory factor analysis demonstrated model fit (χ²/df = 2.184; CFI = 0.947; TLI = 0.932; RMSEA = 0.041), while convergent validity indicated an AVE of 0.563 in Indonesia and 0.589 in Syria, with composite reliability values of 0.891 and 0.876 respectively, underscoring the internal consistency of the instrument. Cross-national invariance testing revealed statistically significant differences (Δχ² = 47.23; p < 0.001), with the mean score of Islamic moderation in Indonesia (M = 4.12; SD = 0.67) surpassing that of Syria (M = 3.84; SD = 0.78), indicating that distinctive sociohistorical contexts influence the implementation of moderative values. Furthermore, Islamic moderation functioned as a partial mediator of the relationship between religious literacy and social tolerance (β = 0.342; p < 0.001 for Indonesia; β = 0.287; p < 0.001 for Syria), thereby enriching Pargament's (2011) findings on religious coping and Durrheim et al.'s (2016) work on intergroup prejudice. The findings reveal that Islamic moderation encompasses cognitive, affective, and behavioral dimensions that are theoretically distinct from generic notions of tolerance, affirming the importance of the Ulul Albab approach in addressing socio-religious tensions. Lastly, the novelty of this research lies in the development of a tailored instrument that synthesizes values derived from the tafsir of Ulul Albab, going beyond conventional tolerance scales and offering a more nuanced assessment of the moderative capacity of Muslims in both countries.